Effect of sun dried whole bulb garlic powder on growth, carcass characteristics and meat quality of commercial broilers - SINGH, JASWINDER; SETHI, A P S; SIKKA, S S; CHATLI, M K; KUMAR, PAVAN (The Indian Journal of Animal Sciences, 2015)
A study was conducted to evaluate the effect of sun dried whole bulb garlic powder as phytogenic alternative to antibiotic growth promoters in broilers. Day-old broiler chicks (225; IBL 80) were randomly distributed to 5 treatments with 3 replicates. The dietary treatments comprises of basal diet as control, antibiotic group receiving 0.1g/kg of oxytetracycline, 1.0,1.5 and 2.0% of sun-dried whole bulb garlic powder (WBGP) added to basal diet. Daily feed intake, weekly body weight and residue left any were recorded to calculate the feed conversion and protein efficiency ratios. At the end of fifth week 2 birds / replicate were sacrificed to determine the carcass characteristics and meat sensory evaluation. Results revealed that supplementation of WBGP at 1.5% improved the body weight, which is statistically comparable with the antibiotic fed group but the feed conversion ratio was significantly lower in 1.5% WBGP supplemented group than the control and antibiotic groups. Dietary treatment does not significantly influence the carcass characteristics except the relative heart weight. Supplementation of WBGP significantly improved the meat quality parameters as compare to control group. From the results of present study, it is concluded that dietary inclusion of 1.5% sun dried WBGP can be used as phytogenic alternative to antibiotic growth promoters in broilers.